[OP.2A.04] EPIGENETIC REGULATION OF HYPERTENSION: STRAIN-SPECIFIC SILENCING OF A RAT ANGIOTENSINOGEN TRANSGENE IN MICE. (September 2017) - Taryma-Lesniak, O.; Munz, M.; Todiras, N.; Todiras, M.; Rabelo, L.; Nunes, V.; Erdmann, J.; Aherrahrou, Z.; Alenina, N.; Bader, M.
Abstract : Objective: The renin-angiotensin system (RAS) is the most important system regulating blood pressure and, therefore, the major target for the treatment of hypertension. Angiotensinogen (AOGEN) is the only precursor of all peptides of the RAS. The role of epigenetic factors in AOGEN regulation still remains unclear. Design and method: In 1992, Kimura and colleagues generated a transgenic mouse overexpressing rat AOGEN under the control of its own promoter (TGM(rAOGEN)123). These mice exhibit increased angiotensin II levels, and, consequently high blood pressure and end-organ damage as early as at 8 weeks of age. We backcrossed this mouse, originally generated on the outbred genetic background, NMRI, to two distinct genetic backgrounds, FVB/N and C57BL/6. Similar to the NMRI background, 123FVB/N mice showed a drastic increase in blood pressure (158.3 ± 3.2 vs 110.1 ± 0.9 mmHg in FVB/N wildtype). However, 123C57BL/6 mice lost the hypertensive phenotype and showed only a mild increase in blood pressure (113.2 ± 0.3 vs 106 ± 0.4 mmHg in C57BL/6 wildtype mice), indicating that the C57BL/6 background has a protective effect. Results: Analysis of the rat AOGEN mRNA levels revealed a drastic downregulation of transgene expression on the C57BL/6 background. To understand the mechanisms leading to transgene silencing we studied epigenetic modifications of the transgene promoter. Indeed, several CpG islands in the 800 bp regulatory region of the rat AOGEN gene were hypermethylated on the C57BL/6 background in comparison to FVB/N. A genome-wide association study in an F2 generation intercross of the two transgenic mouse strains revealed a 6.4 Mb locus, containing 66 genes, on chromosome 13 with significant linkage to the hypertensive phenotype. Conclusions: These data indicate that hypermethylation of the rat AOGEN gene promoter leads to downregulation of its expression and the loss of the hypertensive phenotype on the C57BL/6 background. Further studies are in progress to identify the gene(s) on chromosome 13 responsible for the protective effect.